Working in family firms - Thomas Breda (IZA World of Labor, 2018)
Family firms are ubiquitous in most countries. The differences in objectives, governance, and management styles between those firms and their non-family counterparts have several implications for the workforce, which scholars have only recently started to investigate. Family firms offer greater job security, employ different management practices, have a comparative advantage to avoid conflicts when employment relations are more hostile, and provide insurance to workers through implicit contracts when labor market regulation is limited. But all this also comes at a cost.
Keywords: G34; J31; J33; J63; L26; 330; family firms; wages; job security; working conditions; paternalism